Tailoring basic and acidic properties of MgAl hydrotalcite by fluoride anions: Effect on glycerol oligomerisation - Maderuelo-Solera, Rocío; Ledesma-Muñoz, A.L.; García-Sancho, Cristina; Cecilia-Buenestado, Juan Antonio; Infantes-Molina, Antonia; Mérida-Robles, Josefa María; Maireles-Torres, Pedro Jesús; Moreno-Tost, Ramón (Elsevier, 2023)
In this work, two families of catalysts based on mixed metal oxides derived from MgAl hydrotalcites were synthesized with a Mg/Al molar ratio of 3. On the one hand, in the first family, the fluoride anion was incorporated in the interlayer space by using ammonium fluoride, exploiting the “memory effect” characteristic of hydrotalcites. In the second family, fluoride anions substituted oxides anions in the layer, incorporating directly them during the precipitation of hydroxides, by using cryolite as a precursor for both fluorine and aluminium. The hydrotalcites were transformed into mixed metal oxides by thermal treatment and tested in the glycerol etherification reaction at 230 ºC, in a batch reactor at atmospheric pressure. The hydrotalcites and the corresponding mixed metal oxides were characterized by different experimental techniques, such as X-ray diffraction (XRD), elemental analysis (CHF), N2 sorption at -196ºC, thermogravimetric analysis (ATD-TG), X-ray photoelectron spectroscopy (XPS), temperature-programmed desorption of CO2 and NH3 (CO2-TPD and NH3-DTP) and solid state nuclear magnetic resonace (ssNMR) of 19F. It was found that the mixed metal oxides prepared from hydrotalcites, where fluorine was incorporated in the synthesis step using cryolite, achieved the maximum conversion values and complete selectivity towards diglycerol. Diglycerols were the unique detected products and, in some cases, the formation of triglycerols was also detected.
Keywords: Fluoruro; Hidrotalcitas; Hydrotalcites; Fluoride doping; 19F-ssNMR; XPS; Glycerol oligomerization